Perspectives on the Sources of Heterogeneity in Indian Industry - Lall, Somik V.; Rodrigo, G. Chris (World Bank, Washington, DC, 2014)
The authors examine technical efficiency variation across four industrial sectors in India, using a stochastic production frontier technique. The results are comparable to technical efficiency distribution patterns obtained in other countries. The authors examine heterogeneity in firm-level efficiency against internal, firm-level characteristics and against external characteristics (industry and location). The results suggest that managerial effectiveness significantly influences efficiency and that considerable benefits derive from location within established industrial clusters for particular industries. The methodology and findings indicate that the study of industry-specific technical efficiency patterns is a useful analytical tool for tracking domestic firms' response to liberalization and the advance of market forces. An important policy implication of the authors' results: There is considerable room for efficiency gains through better organization and management of production processes and improved supply chain management, even in the highly organized corporate sector. These gains could be achieved by purely internal learning processes with no extra investment in physical plant or equipment, or with the help of outside consultants, or through business alliances with partners from industrial countries (a rising trend). The results also show that greater technical efficiency correlates with better energy use and higher investments in plant management. How firms can be induced to undertake such investments in the "software" of production is an important issue. Liberalization and globalization are likely to bring significant productivity gains even in low-technology industries as managers gear up to meet the challenges of competition.